Sodium and potassium intercalation into Ta2PdS6 - Hyde, PA; Clarke, SJ (Elsevier, 2023)
Two new phases derived from the layered ternary chalcogenide Ta2PdS6 have been successfully synthesised via the intercalation of sodium or potassium. MTa2PdS6 (M ​= ​Na, K) crystallise in monoclinic space group I2/m (No. 12), Z ​= ​2, with lattice parameters a ​= ​8.1366(7) Å, b ​= ​3.2876(1) Å, c ​= ​15.3279(3) Å, β ​= ​97.407(2)° for NaTa2PdS6, and a ​= ​8.3845(3) Å, b ​= ​3.2955(1) Å, c ​= ​16.7416(8) Å, β ​= ​86.339(3)° in the case of KTa2PdS6. The general structure of the parent phase is retained upon intercalation, with increased unit cell volumes of 17.3% and 33.2% for the Na and K intercalates respectively. SQUID magnetometry shows that both intercalates are net diamagnets, but shows a significant reduction of magnetic susceptibility from Ta2PdS6 due to the increase in a Pauli paramagnetic component due to partial band filling.